2017
DOI: 10.1089/end.2017.0084
|View full text |Cite
|
Sign up to set email alerts
|

CT Texture Analysis of Ex Vivo Renal Stones Predicts Ease of Fragmentation with Shockwave Lithotripsy

Abstract: CTTA metrics entropy and kurtosis have been shown in this experimental ex vivo setting to strongly predict fragmentation by SWL. This warrants further investigation in a larger clinical study for the contribution of CT textural metrics as a measure of stone heterogeneity, along with other known clinical factors, to predict likelihood of SWL success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…So far, urogenital applications of TA included an improvement of accuracy for prostate cancer detection in apparent diffusion coefficient maps 22 , and a distinction of histological subtypes of renal and adrenal tumors on CT 23 . Cui et al 17 and our group 16 have recently demonstrated that 2D-TA can predict successful SWL with moderate accuracy in an in-vitro stone model. In this study we were able to improve previous TA methodology in four important aspects.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…So far, urogenital applications of TA included an improvement of accuracy for prostate cancer detection in apparent diffusion coefficient maps 22 , and a distinction of histological subtypes of renal and adrenal tumors on CT 23 . Cui et al 17 and our group 16 have recently demonstrated that 2D-TA can predict successful SWL with moderate accuracy in an in-vitro stone model. In this study we were able to improve previous TA methodology in four important aspects.…”
Section: Discussionmentioning
confidence: 92%
“…Texture analysis (TA) detects distinct quantifiable differences of stone characteristics that may not be seen in a purely visual analysis. Our group 16 and Cui et al 17 have recently demonstrated that two dimensional (2D) TA can predict successful SWL in an in-vitro stone model. Latest developments in software technology have enabled three dimensional (3D) TA instead of only 2D-TA analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Obese patients and those with a higher body mass index (BMI) may have a larger skin to stone distance revealed during clinical examination, which could lead to unfavorable SWL success rates [12,23]. Some studies highlighted the importance of anatomical location and the architecture of the stones as measured by CT Houns eld units [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary studies have shown that the success rate of SWL for renal stones ranges from 47 to 92% [2][3][4][5][6][7]. This highly variable result is due to various crucial factors, including stone composition and size [8][9][10][11], skin to stone distance [12], lithotripter energy power [13] and frequency [14,15], patient positioning [16], and patient tolerance and respiration [16,17]. Less than half of the administered shockwaves may be accurately focused on the targeted calculus [18], and the excessive energy and shockwaves can cause damage to the parenchyma and adjacent organs.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation can potentially come from the fact that no intra-or interobserver agreement was assessed. However, previous studies on CT and MRI have demonstrated good reproducibility for filtration-histogram-based TA using multicenter clinical validation [37,38], robustness to variation in image acquisition parameters [44][45][46][47], and good inter-and intraoperator repeatability (good intraclass correlation from test-retest technique) [48,49]. The lack of cytological analysis of the cystic fluid can be considered a major limitation.…”
Section: Study Limitationsmentioning
confidence: 99%